Corruption and the Global Economy - Edited by Kimberly Ann Elliott (Washington, DC Institute for International Economics, 1997)
With the end of the Cold War, the pace and breadth of the trends toward democratization, and international economic integration accelerated and expanded globally, this book examines the causes and consequences of corruption, including the impact on development and growth.
Include Economics Table of Corruption
Keywords: Political corruption--Economic aspects -- International business enterprises